STRATEGI PENCITRAAN KOTA (CITY BRANDING) BERBASIS KEARIFAN LOKAL (Studi Kasus di Kota Solo, Jawa Tengah dan Kabupaten Badung, Bali) - Bambang Widodo (Profetik: Jurnal Komunikasi, 2014)
This article is the first result of fundamental grant research about city branding and local wisdom which has conduct for two years in the district of Solo and Badung. The aims of this research were to get a comprehensive description about government understanding of city branding, city branding strategy which is held by the both of district and people image about their city. The datas collected by using depth interview, observation and document analysis. The research result shows that there was a difference betwen the district of Solo and Badung in interpreting and implementing city branding. Solo’s branding was formulated by third party in cooperation with several districts. On the other side, the district of Badung was using their live guidance as their base of city branding.